The potential of microphytobenthos in sediment biostabilisation of aquatic ecosystems: An overview - Redzuan, Nurul Shahida; Milow, Pozi (Bioflux SRL, 2019)
Microphytobenthos represents microscopic primary producers, primarily diatoms that often form heterogeneous biofilms on sediment surface. Microphytobenthos assemblages have been documented and reported to be closely linked with the biostabilisation of the sediment surface in the intertidal flat of Europe. Flood and ebb tides cause vertical movement of the benthic diatoms in the surface of the top sediment, which contributes to stabilizing the sediment. Light, salinity and other environmental stressors further initiate microphytobenthos to move up and down vertically in the surface of the top sediment. Diatoms produce and secrete extracellular polymeric substances in response to their locomotion, which favorably stabilize the sediment surface during high tide immersion. Frequent storms caused by climate change have intensified the erosion problem along coastlines. Unfortunately, structures such as wave breakers and breakwaters that are built along some coastlines have proven to worsen the erosion rate. More environmental and biological-friendly solutions are needed to tackle the erosion problem worldwide. The widely distributed tidal flats and mangrove forests along the coastlines must harbor the diatom species that have biostabilisation potential. This review presents data that supports the biostabilisation of sediment by diatoms, provides information on this process and initiates more studies regarding the potential of microphytobenthos in biologically reducing sediment erosion along the coastlines, rather than structurally. © 2019, BIOFLUX SRL. All rights reserved.